Informatization Expectation with Cloud Computing in China - YANG Zhexi; XUE Huacheng (Institute of Advanced Engineering and Science, 2012)
Cloud computing has been the most popular and promising concept in the new century with no doubt, which is the most important strategy filed to occupy for IT giants. It is said to lead the 3rd IT revolution, so it will affect every organization, enterprise and individual and therefore the process of informatization of China definitely. Literatures about informatization are reviewed in this paper, characters from market angle are concluded, and expectation is drawn to lead Cloud Computing informatization. DOI: http://dx.doi.org/10.11591/telkomnika.v10i4.879